Outsmarted by nootropics?† An investigation into the thermal degradation of modafinil, modafinic acid, adrafinil, CRL‐40, 940 and CRL‐40, 941 in the GC injector: formation of 1, 1, 2, 2‐tetraphenylethane and its tetra fluoro analog. Issue 3 (29th December 2016) - Dowling, Geraldine; Kavanagh, Pierce V.; Talbot, Brian; O'Brien, John; Hessman, Gary; McLaughlin, Gavin; Twamley, Brendan; Brandt, Simon D.
Abstract : 2‐[(Diphenylmethyl)sulfinyl]acetamide (modafinil) is commonly prescribed for the treatment of narcolepsy. Increasing popularity and off‐label use as a cognitive enhancer has resulted in a reputation as an intelligence boosting 'wonder drug'. Common alternatives available from online shops and other retail outlets include 2‐[(diphenylmethyl)sulfinyl]‐ N ‐hydroxyacetamide (adrafinil), 2‐[bis(4‐fluorophenyl)methyl]sulfinylacetamide (CRL‐40, 940), 2‐[bis(4‐fluorophenyl)methyl]sulfinyl‐ N ‐hydroxyacetamide (CRL‐40, 941), and N ‐methyl‐4, 4‐difluoro‐modafinil (modafiendz), respectively. Gas chromatography‐mass spectrometry (GC‐MS) is a common tool used in forensic and clinical analysis but there is a potential for inducing analysis‐related ambiguities. This study reports on the thermal degradation of modafinil, modafinic acid, adrafinil, CRL‐40, 940, and CRL‐40, 941 due to exposure to the heated GC injection port dissolved in a variety of solvents. Key degradation products common to modafinil, modafinic acid, and adrafinil analysis included diphenylmethanol and 1, 1, 2, 2‐tetraphenylethane (TPE), the latter of which was verified by its synthesis and characterization by x‐ray crystallography. The investigated compounds were also characterized by 1 H and 13 C NMR. Diphenylmethane and thiobenzophenone were also identified in some instances. TPE formation was suggested to involve the generation of a benzhydrylium ion and its reaction with the sulfoxide oxygen of the parent compound to give an oxysulfonium intermediate. Correspondingly, the fluorinated TPE analogue was formed during heat‐induced degradation of modafiendz, CRL‐40, 940 and CRL‐40, 941, respectively. When a mixture of modafinil (non‐fluorinated) and modafiendz (fluorinated) were subjected to GC analysis, 4, 4'‐(2, 2‐diphenylethane‐1, 1‐diyl)bis(fluorobenzene) was detected as a third cross reaction product in addition to the two expected TPE analogues. These observations served as a reminder that the seemingly straightforward implementation of GC‐MS analysis can lead to challenges during routine analysis. Abstract : This study reports the thermal degradation of modafinil, modafinic acid, adrafinil, CRL‐40, 940, and CRL‐40, 941, due to exposure to the heated GC injection port. Key degradation products common to modafinil, modafinic acid, adrafinil analysis include diphenylmethanol and 1, 1, 2, 2‐tetraphenylethane (TPE).